2002
DOI: 10.1007/s00203-002-0463-x
|View full text |Cite
|
Sign up to set email alerts
|

The veA gene is necessary for the inducible expression by fructosyl amines of the Aspergillus nidulans faoA gene encoding fructosyl amino acid oxidase (amadoriase, EC 1.5.3)

Abstract: The faoA gene encoding fructosyl amino acid oxidase (FAOD, EC 1.5.3) was isolated from Aspergillus nidulans and characterized. The complete nucleotide sequence of the faoA (fructosyl amino acid oxidase) gene and its cDNA revealed that the faoA gene encodes a 441-amino-acid polypeptide interrupted by five introns. Expression of the A. nidulans faoA gene was inducible by fructosyl propylamine and fructosyl lysine, as is the case for the gene encoding FAOD in other organisms. The faoA gene was not induced by thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It is worth mentioning that in A. nidulans the corresponding gene (faoA) is induced by fructosyl amines and controlled by velvet, which has been identified as a redlight-dependent activator of sexual development and as an inhibitor of asexual development (Jeong et al, 2002). In contrast blu-13 appears to be regulated by blue light and blr dependent.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that in A. nidulans the corresponding gene (faoA) is induced by fructosyl amines and controlled by velvet, which has been identified as a redlight-dependent activator of sexual development and as an inhibitor of asexual development (Jeong et al, 2002). In contrast blu-13 appears to be regulated by blue light and blr dependent.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Jeong et al [33] showed such induction in Aspergillus nidulans requires the veA gene, which is an activator of sexual development. The veA gene alone can also induce fructosyl amine oxidase expression, while its own expression is not affected by Amadori products [33].…”
Section: Fructosyl Amine Oxidasesmentioning
confidence: 98%
“…Based on these and other findings, the VeA protein was designated a positive-acting factor of A. nidulans, promoting the sexual differentiation of this homothallic species. Recent studies have demonstrated a further role of the veA gene product in the regulation of secondary metabolism (10,31), including the control of genes which directly or indirectly participate in carbohydrate metabolism, such as the mannoprotein-encoding gene mnpA (27) and fructosyl amine induction of the faoA gene, which encodes a fructosyl amino acid oxidase activity (28).…”
mentioning
confidence: 99%